2009
DOI: 10.1021/ef9001296
|View full text |Cite
|
Sign up to set email alerts
|

Material Properties Influencing the Oxidation and Ignition Reactivity of Activated Carbons: Thermal Analysis, HRTEM Study, and Statistical Modeling

Abstract: The aim of this work is to understand the influence of textural, chemical, and structural properties on the reactivity of activated carbons toward air. Multiscale organization of activated carbons was studied using high-resolution transmission electron microscopy (HRTEM) and their quantitative structural data, like individual fringe length, interlayer spacing, and proportion of nonstacked layers, were extracted using a specific image analysis procedure. Intrinsic properties like the specific surface area S BET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Accidents occurring with activated carbon beds, especially when removing ketones present in waste air emissions, have been reported previously [7][8][9][10]. In order to approach the combustion of an adsorbent bed due to increase in local temperature, an adsorption of acetone at very high concentration (150 g m −3 ) was performed.…”
Section: Combustion In the Activated Carbon Bedmentioning
confidence: 99%
See 1 more Smart Citation
“…Accidents occurring with activated carbon beds, especially when removing ketones present in waste air emissions, have been reported previously [7][8][9][10]. In order to approach the combustion of an adsorbent bed due to increase in local temperature, an adsorption of acetone at very high concentration (150 g m −3 ) was performed.…”
Section: Combustion In the Activated Carbon Bedmentioning
confidence: 99%
“…The first known incident of bed ignition was related to a small unit of coconut shell carbon recovering cyclohexanone in the late 1940s [2]. Most carbon bed combustion has occurred with ketones, aldehydes, carboxylic acids and organic sulphur compounds [7][8][9][10][11][12][13]. The question of predicting temperature evolution is thus an essential part of designing the safety of an adsorption process, and some results have been published previously [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of Raman spectroscopy and high-resolution transmission electron microscopy (HRTEM), the structural characterization of coals improved a lot. For carbonaceous materials with perfect graphitic structure, only the G band exists in Raman spectra, corresponding to the E 2g symmetrical stretching vibration mode in the aromatic layers. , In other carbonaceous material, the D band, which is related to structure defects, also appears. On the basis of the work of Raman, Li et al showed that defects in ductile-deformed coals exceeded these in brittle-deformed coals.…”
Section: Introductionmentioning
confidence: 99%
“…HRTEM (002 bright field mode) is a direct way to visualize aromatic layers . In this mode, aromatic layers are imaged as fringes. Via quantitative analysis, researchers obtained fringe length and tortuosity from HRTEM images. Fringe length is a measure of the extent of aromatic layers, and fringe tortuosity reflects the wrinkle degree of aromatic layers . Studies on graphene indicated that the wrinkle degree of the sheet was related to the appearance of Stone–Wale (SW) defects. SW defects are induced via in-plane rotation of C–C bonds by 90°, where four hexagons are transformed into two pentagons and two heptagons .…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon is the most widely used adsorbent material and is utilized in a variety of industrial situations . It is critical that all operations utilizing activated carbon maintain the adsorbent temperature below the thermal stability of the carbon to prevent fires, and therefore, care must be taken to properly identify the ignition temperature of the carbon …”
Section: Introductionmentioning
confidence: 99%